A Study of Mushroom Diversity at Siriba Campus, Maseno University Maseno, Kenya - George T. Opande; David M. Musyimi; Tirop C. Sarah (Innovations in Microbiology and Biotechnology Vol. 8, 2022)
About 3500 species of mushroom exist in the whole world. Examples being the ring mushroom, honey fungi, the poisonous amanita, the button mushrooms and the oyster white mushrooms among others. Before this study, no study had been conducted in western Kenya and specifically Maseno University forest ecosystem to show the existing mushroom flora though Mushroom species are known to exhibit different morphological and anatomical structures that could be useful in their identification. This study was therefore initiated to identify and record the available mushroom species in the area because its climatic state allows abundant mushroom growth. This study was conducted at the Maseno University forest ecosystem, located within the coordinates 0\(^°\) 0’ 17.36" S, 34\(^°\) 36’ 1.62" E at an altitude of 1503 meters above sea level. The terrain where the collection was done mainly consisted of sloppy forest vegetation with mean temperature during the collection period ranging between 19\(^°\)C and 21\(^°\)C. Stratified randomized sampling method was used whereby the area of study was divided into portions/ sites. Mushrooms were collected on their vegetative stages and sorted accordingly. The location and substrate on which mushrooms grew were also recorded and all the species collected identified based on their morphological characteristics. Some of the species identified included; Daedalia quercina, Formitopsis gibba, Poliporous cinnabarinus, Xerula radicata, manita rannesces, Lycoperdon echinatum, Laccaria bicolor, Clitocybe gibba, Suillus luteu and Daedalia unicolor. More studies need to be conducted in this forest to identify other unidentified species.